Molecular beam epitaxial growth of InAs/InAlAs quantum wires on Inp (100) substrate - Casco, Ma. Frantessa (National Institute of Physics, College of Science, University of the Philippines Diliman, 2007)
InP-based InAs nanostructures are attracting attention as a good light emitter in the long-wavelength (1.3-1.5 μm) region. Self-assembled quantum wires and quantum dots are achieved by varying growth parameters such as growth temperature, arsenic overpressure, and InAs thickness.